Acute physiological responses during a Brazilian endurance triathlon race - Danielli Mello; Eduardo Borba Neves; Wagner Romão; Antony Santos; Filipe Farias; Thiago Dias; Marcio Sena; Marcos Dias Pereira; Guilherme Rosa; Rodrigo Vale (Desafio Singular, 2020)
Triathlon is one of the most flourishing sports in the world. This study aimed to analyze the acute effects of physiological markers and subjective perception variables in amateur trained athletes. Participated in the present study 8 male endurance triathletes with race experience. The injury markers and oxidative stress parameters were investigated in the blood plasma and measured at baseline and post-race. Heat, comfort, and humidity perception, and Borg ratings of perceived exertion were measured during the baseline, transition area, and post-race. Descriptive and inferential statistics were used with significance set as p<0.05. The variables of injury and muscle fatigue presented a significant increase comparing the baseline and post-race data, CK (p= 0.005; d= 5.7), LDH (p= 0.004; d= 1.3) and lactate (p< 0.001; d= 7.2). It was observed a significant increase in CP (p= 0.021; d= 2.2) and a significant decrease in DPPH (p= 0.002; d= -1.4) in post-race, no significant changes in LP (p= 0.217; d= 0.6) and TT (p= 0.881; d= -0.1) oxidative stress markers was verified. A significant increase (Δ% = 30.95, p = 0.001; d = 6.8) was observed in urine temperature and color (range [1-7], p = 0.039). Even with the significant increase in fatigue, with a significant increase in the injury markers, oxidative stress markers suggested a good antioxidant defense. It was observed an increase in exertion and heat perception, as well as a reduction in heat comfort and skin wetness.